2011 International Conference in Electrics, Communication and Automatic Control Proceedings - Chen, Ran (Lecture Notes in Electrical Engineering, 2012)
This two-volume set contains the very latest, cutting-edge material in electrics, communication and automatic control. As a vital field of research that is highly relevant to current developments in a number of technological domains, the subjects it covers include micro-electronics and integrated circuit control, signal processing technology, next-generation network infrastructure, wireless communication and scientific instruments. The aim of the International Conference in Electrics, Communication and Automatic Control, held in Chongqing, China, in June 2011 was to provide a valuable inclusive platform for researchers, engineers, academicians and industrial professionals from all over the world to share their research results with fellow scientists in the sector. The call for papers netted well over 600 submissions, of which 224 were selected for presentation. This fully peer-reviewed collection of papers from the conference can be viewed as a single-source compendium of the latest trends and techniques in the field, making it a must-have resource for anyone wanting to stay abreast of developments.